1984
DOI: 10.1039/f19848000013
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron-scattering study of microemulsions stabilised by aerosol-OT. Part 1.—Solvent and concentration variation

Abstract: Small-angle neutron-scattering (SANS) measurements have been made for a series of aerosol-OT (A0T)-stabilised water-in-oil microemulsions. The intensity pattern has been used to extract a value for the radius of the water core, rw, using D,O to provide the required contrast profile. In heptane the radii are found to follow an approximately linear relationship with respect to the [D,O]/[AOT] concentration ratio, R. At 20 OC, and R = 20, the structure of the water-droplet system is dependent on the hydrocarbon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(97 citation statements)
references
References 0 publications
7
90
0
Order By: Relevance
“…observed in water-in-oil microemulsion systems. 133,134 Unfortunately in many cases, the same effect is not seen. Cason et al 47 and then Kitchens et al 63 found that at any given value of w 0 , the same size nanoparticles can be synthesized, if left for sufficient time for the reaction to go to completion ( Figure 5).…”
Section: Reagent Concentrationmentioning
confidence: 88%
“…observed in water-in-oil microemulsion systems. 133,134 Unfortunately in many cases, the same effect is not seen. Cason et al 47 and then Kitchens et al 63 found that at any given value of w 0 , the same size nanoparticles can be synthesized, if left for sufficient time for the reaction to go to completion ( Figure 5).…”
Section: Reagent Concentrationmentioning
confidence: 88%
“…Aqueous AOT reverse micelles can be characterized over a wide range of water and surfactant concentrations by a single parameter, which is proportional to the micellar radius. 12, 13 These aggregates have been found to be relatively monodisperse in solution and spherical in shape down to very low water concentrations. 14 The spherical aggregates, which are the focus of this study, range in the diameter of the aqueous core from about 0.5 nm to more than 10.0 nm.…”
Section: Introductionmentioning
confidence: 99%
“…5 Experimental techniques that have been used to characterize the AOT reverse micelles include light scattering, 41,42 photon correlation, 12 IR spectroscopy, 23,[43][44][45][46][47] NMR, 11,22,[48][49][50][51][52] probe fluorescence, 10,21,53-61 calorimetry, 62,63 small-angle neutron scattering (SANS), 13,14,64 and quasi-elastic neutron scattering. 65,66 While many of these techniques provide information about the structure and properties of reverse micelles, a fundamental dispute remains about the structure of water in the micellar interior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in this parameter are accompanied by changes in the size of the inner water cavity of reversed micelles [30,31]. Maximal enzyme catalytic activity in reversed micelles is observed at a particular degree of surfactant hydration, namely when the size of the inner cavity corresponds to that of the entrapped protein (general regularities of the phenomenon are discussed in [17]).…”
Section: Resultsmentioning
confidence: 99%